A Study Review Between Ss430 And Crofer 22 Apu Solid Oxide Fuel Cell (Sofc) Interconnect After Spinel Coating Produced By Electrophoretic Deposition - KAHA, ARFIZAN; AZMI, MOHD AZHAM (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The study of multiple review on interconnect spinel coating for solid oxide fuel cell (SOFC) based on stainless steel SS 430 and Crofer 22 APU has been considered in this study. The objectives for this research are to review the fabrication method of solid oxide fuel cell through stainless steel 430 (SS430) and Crofer 22 APU as interconnect material mainly via electrophoretic deposition technique (EPD) based on previous studies and to identify the influence of applied voltage and coating duration during the process of coating as well as to advise the appropriate voltage and coating duration for the required Area Specific Resistance (ASR) value and the coating thickness for the solid oxide fuel cell (SOFC) application. In order to understand the best possible in order to achieve the requirements for interconnect SOFC, a review on previous studies has been conducted. This process is followed by characterization of coated and oxidized SS430 substrate and Crofer 22 APU substrate. These review characterization include phase analysis, surface morphology analysis, elemental distribution analysis and performance of area specific resistance (ASR). The result for this experiment show that, ss430 substrate is most suitable compare to crofer 22 apu. To increase the EPD can be examined by adding parameters to the applied voltage and time deposition.